PERAN PEMBELAJARAN ORGANISASI DALAM MENINGKATKAN KAPASITAS INOVASI KARYAWAN MENGHADAPI PERUBAHAN - Riza Fitriana; Agus Mandar; Padil Putra Firani (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2025)
Rapid changes and uncertainties, such as those experienced during the Covid-19 pandemic, require organizations to have good adaptability. The ability to respond to these changes is inseparable from a culture of knowledge sharing among members of the organization that fosters a climate of continuous learning. A learning organization is a concept that empowers its members to continuously develop their capacities, share knowledge, and learn together consistently. This concept is not only useful for dealing with current changes, but also serves as a long-term investment that encourages knowledge enhancement, competency, sustainable performance, innovation, and the ability to cope with future changes. This study uses a descriptive analytical method with a literature review approach to analyze the concept of organizational learning. The results show that organizational learning is very important in dealing with various organizational problems, increasing innovation capacity, and achieving maximum company performance. Organizational learning has a significant effect on innovation and organizational performance through the process of acquiring, sharing, using, and storing knowledge involving three dimensions: individuals, groups, and organizations. To achieve effective organizational learning, management support, an appropriate organizational structure, a culture of collaboration, and the use of technology to accelerate knowledge transfer are needed in order to gain a sustainable competitive advantage.